Photoreduction of carbon dioxide under visible light by ultra-small Ag nanoparticles doped into Co-ZIF-9. (14th May 2018) - Chen, Mengmeng; Han, Lu; Zhou, Jie; Sun, Chunyi; Hu, Chengying; Wang, Xinlong; Su, Zhongmin
Abstract: Metal–organic frameworks (MOFs) are well-known porous materials able to adsorb CO2, and their performance in CO2 reduction has attracted much attention from researchers. A classical Co-MOF, Co-ZIF-9, has been proposed as a novel photocatalyst for reducing CO2 into chemical feedstocks. Herein, Co-ZIF-9 with a rod-like structure was obtained through reflux. Ultra-small silver nanoparticles (Ag NPs, smaller than 5 nm) were doped into Co-ZIF-9 by the photodeposition method. With the assistance of a photosensitizer, the resultant composite Ag@Co-ZIF-9 shows catalytic reactivity in converting CO2 into CO under visible light irradiation. Compared with bare Co-ZIF-9, the photocatalytic performance of Ag@Co-ZIF-9 increases by more than twofold (around 28.4 μ mol CO) and the selectivity is enhanced by about 20% (22.9 μ mol H2 ) for 0.5 h of irradiation. This demonstrates that Ag NPs doping may provide a possible way to promote the efficiency and selectivity of MOF materials in CO2 photoreduction.